2010
DOI: 10.1186/1471-2458-10-612
|View full text |Cite
|
Sign up to set email alerts
|

Increasing reports of non-tuberculous mycobacteria in England, Wales and Northern Ireland, 1995-2006

Abstract: BackgroundNon-tuberculous mycobacteria have long been identified as capable of causing human disease and the number at risk, due to immune-suppression, is rising. Several reports have suggested incidence to be increasing, yet routine surveillance-based evidence is lacking. We investigated recent trends in, and the epidemiology of, non-tuberculous mycobacterial infections in England, Wales and Northern Ireland, 1995-2006.MethodsHospital laboratories voluntarily report non-tuberculous mycobacterial infections to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
134
3
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(161 citation statements)
references
References 12 publications
17
134
3
7
Order By: Relevance
“…Although we were unable to determine the true prevalence of disease caused by these organisms in the state of Rio de Janeiro, the current study confirmed an increasing frequency of patients referred with NTM lung disease. In some industrialized countries, the prevalence of NTM has been found to be increasing ( 5 , 17 ), although it remains unclear whether this increase is related to increasing awareness of physicians that leads to more frequent diagnosis, to improved laboratory capacity, or to a combination of both factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we were unable to determine the true prevalence of disease caused by these organisms in the state of Rio de Janeiro, the current study confirmed an increasing frequency of patients referred with NTM lung disease. In some industrialized countries, the prevalence of NTM has been found to be increasing ( 5 , 17 ), although it remains unclear whether this increase is related to increasing awareness of physicians that leads to more frequent diagnosis, to improved laboratory capacity, or to a combination of both factors.…”
Section: Discussionmentioning
confidence: 99%
“…Global geographic variability in M. kansasii has been noted; a high prevalence of M. kansasii lung disease occurs in Western Europe, Switzerland, and the United Kingdom ( 17 , 21 23 ). In Brazil, available data suggest regional differences in species distribution, although distinct study populations and methods limit comparability of estimates.…”
Section: Discussionmentioning
confidence: 99%
“…In the study from the Netherlands, the increase was mainly caused by a rise in M. avium and M. gordonae isolates from pulmonary samples and it was most pronounced in patients >40 years old [3]. A study from the UK showed that the increase in NTM reports was mainly in pulmonary specimens and people aged >60 years, with M. gordonae showing the biggest increase but MAC remaining the most commonly reported species [14]. In Denmark, the rising trend in NTM isolation was less obvious but the incidence of NTM disease had increased, especially in elderly [4].…”
Section: Pulmonary Isolatesmentioning
confidence: 99%
“…For example, in most of Asia and New Zealand after MAC, RGM have generally been the most frequently identified species but India reports no PNTM due to MAC and attributes 40% to M. fortuitum and 33% to M. kansasii [34]. In Britain, MAC (43%), Mycobacterium malmoense (14%) and M. kansasii (13%) were the most frequently isolated species from respiratory specimens [35].…”
Section: Epidemiologymentioning
confidence: 99%